Hukum Penyediaan Jasa Uang Kertas Peribadatan Perspektif Fatwa DSN-MUI Nomor 112/DSN-MUI/IX/2017 Tentang Akad Ijarah - Siti Hajar Arifah; Tetty Marlina Tarigan (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Mu`amalah al-ijarah transactions are permitted because they have many benefits for humanity, both in the form of objects (al-ijarah `ala al-a`yan) and in the form of services (al-ijarah `ala al-a`mal). The Tanjung Gusta Medan community carried out al-ijarah transactions in providing services for making paper money for Buddhist worship, even though it was clear that the matter was closely related to the faith and could violate Islamic law. This type of research is qualitative, the primary data sources are the results of observations and interviews, as well as DSN-MUI Fatwa Number 112/DSN-MUI/IX/2017 concerning the Ijarah Agreement. The research results showed that the motivation of the people of Tanjung Gusta Medan in providing services was due to several reasons, including because there was no work, there were no definite prohibitions, for reasons of tolerance. The concept of al-Ijarah states that the practice of mu`amalah in order to gain benefits from the presence of `iwadh (substitute), is permissible, and it is ensured that the object of the transaction is not something haram. The law on providing services for making banknotes for Buddhist worship from the perspective of DSN-MUI Fatwa Number 112/DSN-MUI/IX/2017 is haram, while the transaction practices carried out are void, because they violate Islamic law.